Perbedaan konsumsi junk food melalui pemesanan daring dan aktivitas fisik pada status gizi mahasiswa kedokteran - Mellinia Wahyu Nurliesa; Agustina Arundina Triharja; Iit Fitrianingrum (Faculty of Medicine, Universitas Andalas, 2023)
Objective: To determine the differences between the frequency of consumption of junk food through online food ordering and physical activity with nutritional status in students of the Faculty of Medicine, Tanjungpura University. Methods: Cross-sectional analytic study and total sampling technique involved 99 students of the Faculty of Medicine, Tanjungpura University. The research measuring tools used the Junk Food Untan Questionnaire Online Ordering (JUQOO) to measure the frequency of junk food consumption through online food ordering made by researchers, the Global Physical Activity Questionnaire (GPAQ) to measure the level of physical activity, and the Self Report Recall Anthropometry sheet to measure the level of body mass index calculation. The Data were analyzed by univariate and bivariate using Kruskal-wallis test. Results: Based on the Kruskal-Wallis test between nutritional status and the frequency of consumption of junk food through online food ordering (p=0,674) and the level of physical activity (p=0,242). Conclusion: There are no significant differences between the frequency of consumption of junk food through online food ordering and physical activity with nutritional status in students of the Faculty of Medicine of Tanjungpura University.